Vitamins and minerals and their role in cancer: a comprehensive review - Garutti, Mattia; de Scordilli, Marco; Alberti, Martina; Mazzeo, Roberta; Michelotti, Anna; Fagioli, Sofia; Del Conte, Alessandro; Casirati, Amanda; Caccialanza, Riccardo; Bartolini, Enrico; Puglisi, Fabio (Frontiers in Nutrition, 2026)
Cancer remains a leading cause of morbidity and mortality worldwide, influenced by genetic, environmental, and lifestyle factors, including nutrition. This review explores the role of vitamins and minerals in cancer prevention and management, highlighting their critical functions in immune response, DNA synthesis, cellular repair, and antioxidant defense. Vitamins such as A, C, D, E, and the B-complex group, along with minerals like calcium, magnesium, and zinc, are essential for maintaining health and managing oncologic diseases. Cancer patients are often at risk of micronutrient deficiencies due to disease and treatment-related factors; addressing these deficiencies through dietary interventions or supplementation may enhance immune function, reduce treatment-related side effects, and improve overall quality of life. In this review, we comprehensively discuss the biology and physiology of vitamins and minerals with a specific focus on cancer while providing a practical overview of recognizing and managing deficiencies. Furthermore, aligned with the principles of culinary medicine, we have developed a set of recipes for patients and caregivers to manage hypokalemia and hypocalcemia, which are particularly common in clinical practice, aiming to offer useful tools for clinicians and dietitians.